Between colonising waters and extracting forest fronts: Entangled eco-frontiers in the Usumacinta River Basin. (June 2022) - Laako, Hanna; Kauffer, Edith
Abstract: The eco-frontier concept has addressed the processes of certain territories that are subject to ecological concern and appropriation of different actors. This study approaches the underexplored interaction with the frontier. The article sharpens the focus on the relations between the eco-frontier and the frontier as both a naturally rich periphery with importance to political centres and as an advancing front. The research discusses empirical results in the case of the transboundary Usumacinta River Basin (URB), which extends from Guatemala's highlands and lowlands through three Mexican states to the Gulf of Mexico. Three historical stages of eco-frontiers—exploratory, epistemic, and institutionalised—are identified in the URB. Its entangled eco-frontiers transform wildernesses and waters to forest ecosystems with inhabitants both spatially and mentally, yet contain some colonial, geopolitical, and global components. This article suggests that the eco-frontiers are fundamentally created because of contemporary frontier dynamics.